Le même et l’autre - Agnès Grivaux (Recherches Germaniques)
The confrontation between Adorno and Foucault has given rise, for an extended period of time, to a renewed, albeit mixed, interest. Whereas in Germany and in the Anglo-Saxon world several authors are working on this issue, this is not so much the case in France, despite the new dynamism of studies dealing with the first Critical Theory and Foucault’s heritage. This article aims at elucidating some of the causes of this phenomenon, starting from the following hypothesis: confronting Adorno with Foucault in the French context is difficult, not because of the divergences between these two authors, but rather because of their convergence with regard to the critique of modern rationality. This convergence raises a major difficulty: their critiques of reason, even if very similar, lead to two distinct concepts of unreason, which are related to their understanding and appraisal of psychoanalysis. This article intends to address this difficulty and propose the outlines of a novel way of interrogating the confrontation between Adorno and Foucault.